Xenobiotic transport across isolated brain microvessels studied by confocal microscopy - Miller, David S.; Nobmann, Stephanie; Fricker, Gert (Molecular pharmacology, 2000)
To identify specific transporters that drive xenobiotics from central nervous system to blood, the accumulation of fluorescent drugs was studied in isolated capillaries from rat and pig brain using confocal microscopy and quantitative image analysis. Luminal accumulation of daunomycin and of fluorescent derivatives of cyclosporine A (CSA) and ivermectin was concentrative, specific, and energy-dependent (inhibition by NaCN). Transport was reduced by PSC 833, ivermectin, verapamil, CSA, and vanadate, but not by leukotriene C4(LTC4), indicating the involvement of P-glycoprotein. Luminal accumulation of the fluorescent organic anions sulforhodamine 101 and fluorescein methotrexate was also concentrative, specific, and energy-dependent. LTC4, chlorodinitrobenzene, and vanadate reduced transport of these compounds, but PSC 833 and verapamil did not, indicating the involvement of a multidrug resistance-associated protein (Mrp). Immunostaining localized P-glycoprotein and Mrp2 to the luminal surface of the capillary endothelium and quantitative polymerase chain reaction showed Mrp1 and Mrp2 expression. Finally, the HIV protease inhibitors saquinavir and ritonavir were potent inhibitors of transport mediated by both P-glycoprotein and Mrp. These results validate a new method for studying drug transport in isolated brain capillaries and implicate both P-glycoprotein and one or more members of the Mrp family in drug transport from central nervous system to blood.